The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2174/187152811794352114
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Gr1+CD11b+ Population in Spleen of Dextran Sulfate Sodium Administered Mice Works to Repair Colitis

Abstract: Dextran sulfate sodium (DSS) is commonly used in rodent IBD models to chemically induce acute intestinal inflammation. The acute course of colitis includes colon tissue damages and recovery from wounded tissues. As skin wound repair was delayed by splenectomy, we asked whether splenectomy would induce the delay of colonic wound healing. In splenectomized mice, body weight recovery, disease score and colon length were delayed. Surprisingly we found a great increase of Gr1+CD11b+ cells in spleen and bone marrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 0 publications
6
39
0
1
Order By: Relevance
“…In addition to IL-6, various chemokines guiding neutrophil recruitment were found among the most upregulated genes in our NGS studies addressing targets of IL-36R signalling in colonic fibroblasts. Although the role of neutrophils in experimental colitis und wound healing may be dependent on the molecular and cellular context, there is substantial evidence that they can contribute to a regenerative function upon intestinal mucosal damage 38 39. Moreover, deficiency in CXCL1 was connected with increased susceptibility to acute colitis40 which is in accordance with the observations in our work.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to IL-6, various chemokines guiding neutrophil recruitment were found among the most upregulated genes in our NGS studies addressing targets of IL-36R signalling in colonic fibroblasts. Although the role of neutrophils in experimental colitis und wound healing may be dependent on the molecular and cellular context, there is substantial evidence that they can contribute to a regenerative function upon intestinal mucosal damage 38 39. Moreover, deficiency in CXCL1 was connected with increased susceptibility to acute colitis40 which is in accordance with the observations in our work.…”
Section: Discussionsupporting
confidence: 91%
“…Neutrophils are important in wound healing and the maintenance of homeostatic processes through their phagocytosis of damaging cellular debris as well as through the secretion of growthpromoting factors such as vascular endothelial growth factor (VEGF), lipoxins, and protectins (257). Some studies have reported that depletion of Gr1 ϩ CD11b ϩ cells, including neutrophils, exacerbates mouse models of colitis, suggesting a protective role for neutrophils (260,261). However, other studies have demonstrated the opposite effect (262), perhaps due to differences in neutrophil depletion methods.…”
Section: Ulcerative Colitis Pathophysiologymentioning
confidence: 99%
“…These results are correlated with our previous work, which showed upregulation of the GR-1 + CD11b + population in the spleen of DSS-treated mice. DSS also produces ROS in the intestine and induces neutrophil migration [18,19]. The transplantation of GR-1 + CD11b + cells in the early phase of wound healing induces early recovery of wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that Gr1 + CD11b + cells increased in the spleen of dextran sulphate sodium (DSS)-treated mice during the recovery phase and splenectomy worsened the colitis [18].…”
Section: Introductionmentioning
confidence: 99%